Rare case of Richter syndrome with testicular involvement successfully obtained good prognosis with rapid operation and immunochemotherapy. Issue 4 (17th June 2019) - Kawase, Kengo; Naiki, Taku; Naiki‐Ito, Aya; Yanada, Masamitsu; Ikegami, Yosuke; Ota, Yuya; Hattori, Tatsuya; Matsuyama, Nayuka; Hamakawa, Takashi; Maruyama, Tetsuji; Yasui, Takahiro
Abstract : Introduction: Richter syndrome refers to the transformation from chronic lymphocytic leukemia to assaultive lymphoma, often a diffuse large B‐cell lymphoma, and has a greatly poor prognosis. Richter syndrome is characterized by rapidly growing lymphadenopathy but rarely presents with extra‐nodal involvement, common sites being the digestive tract, lungs, kidneys, and central nervous system. However, Richter syndrome with testicular involvement is extremely rare. Case presentation: Herein we report a very scare case of a male at the age of 72 with Richter syndrome and testicular involvement, diagnosed by the investigation of bilateral scrotal swellings. The patient had attained disease‐free survival for over a year with rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone, and the intrathecal administration of chemotherapeutic agents after diagnosis by immediate orchiectomy. Conclusion: An early pathological diagnosis by immediate orchiectomy and the early initiation of induction immunochemotherapy may be good prognostic factors in Richter syndrome involving the testes.